C9orf72 Disease-Related Foci Are Each Composed of One Mutant Expanded Repeat RNA. Issue 2 (16th February 2017) - Liu, Jing; Hu, Jiaxin; Ludlow, Andrew T.; Pham, Jacqueline T.; Shay, Jerry W.; Rothstein, Jeffrey D.; Corey, David R.
Summary: The chromosome 9 open reading frame 72 ( c9orf72 ) gene contains a hexanucleotide (GGGGCC) repeat expansion responsible for many cases of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The mutant intronic RNA forms "foci" within nuclei, but the connection between transcript expression, foci, and biochemical disease mechanisms is unclear. Knowing the absolute numbers of cellular RNAs, in any system, is important for understanding the molecular mechanisms of natural physiology, disease, and drug action. Absolute numbers, however, are rarely determined, and this absence is a major impediment to understanding complex systems. Using quantitative methods, we demonstrate that foci are single RNA molecules. Most cells have no foci while 1%–2% have more than ten. Knowing the number of disease-causing molecules may contribute to understanding ALS and FTD pathology and successful drug discovery. More broadly, our data suggest that small numbers of RNA molecules may have a sizable impact on disease. Highlights: Quantitative biochemical link between RNA numbers and disease Less than four mutant c9orf72 molecules per cell on average ∼1:1 correspondence between c9orf72 foci and mutant intronic RNA Small numbers of disease RNA molecules can have major consequences Abstract : Knowing absolute numbers of cellular RNAs is critical for understanding molecular mechanism. The c9orf72 gene is a suspected cause of ALS. Liu et al. find that a handful of mutant c9orf72 transcripts are present per cell. Small numbers of RNA molecules may have a big impact on disease.